The structuring of work in organizations - Cohen, Lisa E.; Burton, M. Diane; Lounsbury, Michael (Research in the sociology of organizations ;, 2016)
Differences in management behavior across organizations are attributed to differences in priorities and objectives or differences in the style and preferences of the individuals involved. This volume challenges this image by attending to the extra-organizational and extra-individual forces that shape and constrain how work is structured in organizations. The authors focus their attention on work within and between organizations and emphasize the ways in which the jobs are defined, the power and autonomy they engender, the opportunities that are afforded, and the constraints that are imposed, are continuously contested not only at the individual level, but also at a more aggregate and collective level. This volume is the product of an interdisciplinary gathering of scholars convened with generous support of the Canadian Social Science and Humanities Research Council. It presents new theoretical and empirical papers that examine aspects of the changing nature of jobs and work in organizations from multiple perspectives and methodologies.